Single cell atlas of cd45+ cells in angiotensin II-induced hypertension. (3rd October 2022) - Crespo, E; Nosalski, R; Park, I; Goddard, M; MacDonald, L; McBride, M W; Monaco, C; Maffia, P; Otto, T; Guzik, T
Abstract:  : Hypertension has been recently identified as an inflammatory disease. Immune cell infiltration is a characteristic feature in the vasculature and the kidneys in experimental hypertension, but the unique nature of such inflammatory infiltrates has not yet been comprehensively characterised. Accordingly, we aimed to provide in-depth characteristics of immune cells in the vasculature and the kidneys in experimental hypertension. To achieve this, we used single-cell RNA-sequencing of leukocytes (CD45+ cells were sorted) using the 10x Genomics platform in the aortas and the kidneys of male 12-week-old C57BL/6J mice (n=16–17/group) upon AngII (490 ng/min/kg) or sham buffer 14-day infusion, using osmotic minipumps. Samples were pooled to analyse three independent replicates. Bioinformatics analysis used Seurat/R to identify immune cell subpopulations and characterise differentially expressed genes (DEGs), pathways, and interactions signatures. Ang II infusion increases the total number of CD45+ leukocytes in the aorta (346.7±89.1 vs. 1210±214.3; p=0, 048), while in the kidneys, this was much less pronounced (1.1±0.5 fold vs. sham). Fifteen leukocyte populations/clusters were identified in the aorta and kidney based on their unique markers. In the aorta, shifts in numerous populations were evident, with the most significant differences in tissue-resident macrophages and activated tissue-resident macrophages, monocyte-derived dendritic cells and NK cells (Figure 1). Kidneys did not display such profound changes. The transcriptomic profile analysis showed 767 significant DEGs in the aorta and only 35 in the kidney. CellChat analysis also indicated more robust interactions between the immune cells in the aorta than in kidneys. These included Ifitm1, Apoe, Il1b, and C1q a/b/c, which were shared between aorta and kidney and may play an immunoregulatory role, affecting smooth muscle cell proliferation and arterial vascular remodelling. Top up-regulated leukocyte genes in the aorta included Ccl8, Ccl3, Cxcl2, Lyz2, and Spp1, while in the kidney, Cd74, Cst3, Fos, Fcer1g, Tyrobp, and Ccl4. GO pathway signatures of aortic leukocyte DEGs revealed pathways related to leukocyte migration, cytokine production, T cell activation, and leukocyte activation and adhesion. Cell-specific analysis showed that macrophage subpopulations most strongly increased in Ang II-induced hypertension displayed the most pronounced changes in the transcriptome profiles and cell-cell interactions. Comprehensive single-cell RNA sequencing identifies tissue-resident macrophages, monocyte-derived dendritic cells, and NK cells as most affected leukocyte subpopulations in hypertensive vasculature. Differentially expressed genes support the role of these cells in vascular remodelling and propagation of inflammation, further supporting the identification of these cells as potential future targets for therapeutic interventions in hypertension. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Council